PENGARUH DEBT TO EQUITY RATIO, CURRENT RATIO, RETURN ON ASSET DAN NET PROFIT MARGIN TERHADAP HARGA SAHAM PERUSAHAAN - Shelly Safitri; Nanu Hasanuh (Jurnal Akuntansi dan Bisnis, 2025)
This research investigates the influence of the debt-to-equity ratio, current ratio, return on assets, and net profit margin on stock prices. The study specifically focuses on pharmaceutical companies listed on the Indonesia Stock Exchange (IDX) between 2019 and 2023. By applying a purposive sampling technique, six pharmaceutical sub-sector companies that met the selection criteria were chosen, resulting in a total of 30 observational data points.Utilizing SPSS version 26, the study applies multiple linear regression analysis to evaluate the data. Initial stages of the multi-step analytical process involve descriptive analysis, classical assumption testing, and hypothesis testing using both t-tests and F-tests. The findings indicate that the debt-to-equity ratio, current ratio, and net profit margin significantly impact stock prices, whereas return on assets does not show a measurable effect. In addition to emphasizing the financial factors relevant to investment decision-making, the results provide valuable insights for stakeholders and investors in the pharmaceutical sector.